Deteksi Plak Gigi dan Edukasi Kebersihan Gigi pada Murid Sekolah Dasar di Kota Surakarta sebagai Upaya Preventif Karies Dini - Saptiwi, Betty; Susanti, Widia; Pujiyati, Alfiyah; Cilmiaty, Risya; Prayitno, Adi; Wardhani, Damiana Tribhuwaneswari Mahendra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2026)
Dental caries remains one of the most persistent health problems among children, frequently triggered by plaque accumulation due to poor oral health knowledge and ineffective toothbrushing techniques. This community service program aimed to measure the effectiveness of dental health education combined with a group toothbrushing practice on improving knowledge and reducing dental plaque index among fourth-grade students at SD Negeri Wonosaren, Surakarta (n=40). The program was implemented using a one-group pretest-posttest pre-experimental design, comprising a knowledge-level questionnaire and visualization of dental plaque using a disclosing agent based on the Silness & Löe Plaque Index. Results showed that the mean knowledge score increased from 51.25 to 88.40, a relative improvement of 72.5%, exceeding the minimum target improvement of 70%. The plaque index also improved: the proportion of students in the good category increased from 15.0% (6 students) to 72.5% (29 students), while the poor category was fully eliminated (0.0%). These findings demonstrate that combining interactive education with group toothbrushing practice effectively enhances children's cognitive knowledge and oral hygiene skills, and may serve as a replicable model for early caries prevention in other elementary schools.